Health-related quality of life and psychological status of women with primary Sjögren's syndrome: A cross-sectional study of 304 Chinese patients. Issue 50 (December 2017) - Liu, Zhaoxiang; Dong, Zhenhua; Liang, Xiaochun; Liu, Jinhe; Xuan, Lei; Wang, Jing; Zhang, Gaili; Hao, Weixin
Abstract : Abstract: Patients with primary Sjögren syndrome (pSS) always suffer from dryness, pain, and fatigue caused by the involvement of multiple different systems or organs. The uncomfortable disease symptoms, the consequent disability, and the side effects of therapeutic drugs decrease the quality of life and lead to emotional problems. We investigated the health-related quality of life and psychological status of a large cohort of women patients with pSS and associated factors. A total of 304 women with pSS referred to Peking Union Medical College Hospital during 2011 and 2014 were included. The internationally recognized Short Form (36) Health Survey (SF-36) was used to assess patients' quality of life; a higher score indicated a better quality of life. Patients' psychological status was assessed by the Hospital Anxiety and Depression Scale (HADS), and higher scores predicted more anxiety or depression. Patients with pSS had remarkably lower SF-36 scores. The Hospital Anxiety Scale (HAS) and Hospital Depression Scale (HDS) scores of the pSS patients (7 [4, 10] and 6 [3, 10], respectively) were significantly higher than that of patients with other internal diseases (3.37 ± 2.81 and 3.83 ± 3.14; both P < .001). Negative predictors of quality of life were: pain (physical condition, β = –0.225; P < .001); fatigue (physical condition, β = –0.298; P < .001; and mental condition, β = –0.319; P < .001). Risk factors for anxiety were: young age (β = –0.059; P = .035); pain (β = 0.025; P = .028); or fatigue (β = 0.029; P = .004). Risk factors for depression were: xeroderma (β = 0.030; P = .003); pain (β = 0.022; P = .047); or fatigue (β = 0.033; P = .001). Patients with pSS have a low quality of life with anxiety and depression. Pain and fatigue are primary factors for lower quality of life, which cause more anxiety and depression.